1975
DOI: 10.1111/j.1471-0528.1975.tb00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Oestrogen Therapy for Labial Adhesions in Children

Abstract: Summary Labial adhesions separated spontaneously after one month of the topical oestrogen therapy in 22 (88 per cent) out of 25 children. This treatment was safe, painless, without significant complications and of lasting value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…2,7 Although there is no consensus for the duration of treatment with topical estrogens, common accepted treatment protocol consists two or three times daily administration of topical estrogens for two weeks. 3 Warm sitz baths and introital hygiene are also advised.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 Although there is no consensus for the duration of treatment with topical estrogens, common accepted treatment protocol consists two or three times daily administration of topical estrogens for two weeks. 3 Warm sitz baths and introital hygiene are also advised.…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric age group, a number of therapeutic regimes have been proposed. These include blunt and/or sharp dissection under anesthesia [16,17], manual separation with/without anesthetic [20], application of topical estrogen [12,18,19,21], and oral estrogen [22].The success rate in any of the regimes has been shown to be as high as 90% with the rate of recurrence after surgical or manual procedures ranging from 14 to 20%. In those using topical estrogen, recurrence was rarely seen.…”
Section: Discussionmentioning
confidence: 99%
“…Opipari (12) recommended treatment with topical estrogen for 4 to 12 weeks. Aribarg (13) reported that, out of 25 girls with severe adhesion of the labia minora, 22 (88%) of the patients were treated successfully by topical estrogen within 1 month.…”
Section: Discussionmentioning
confidence: 99%